KONSEPSI HARTA BERSAMA DAN PENGUASAANNYA MENURUT UNDANGUNDANG PERKAWINAN DAN KITAB UNDANG-UNDANG HUKUM PERDATA - Eman Sulaiman (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
This article describes the Conception of Joint Assets and Their Mastery According to the Marriage Law and the Civil Code. From the results of the discussion obtained an understanding that joint property in Law Number 1 of 1974 concerning Marriage, is limited only to assets obtained during marriage, while assets that are brought before each marriage are called luggage. However, joint property in the Civil Code is not limited to goods (assets) obtained during marriage, but also includes all assets and liabilities (debts), which are held before the marriage takes place, then legally the unity of assets is formed at the time of marriage take place, as long as there is no marriage agreement about that. The management of joint assets in Law number 1 of 1974 needs to be distinguished first whether it is shared property or luggage. If it is shared property, then all legal actions both by the wife and by the husband must be with the agreement of the wife or husband. This can be understood because Law No. 1 of 1974 contains a principle of equality between husband and wife. But it is different for each inheritance to act individually before. While the mastery of shared assets in the Civil Code is entirely in the hands of the husband, the husband can do legal actions without the consent of the wife.